Timeline of the Summer World Polonia Games (1934-2015) - Leonard Nowak; Maria Alicja Nowak (Jan Długosz University in Częstochowa, 2019)
This paper provides a timeline of the 81-year history of the organization of the summer Polonia Sports Games in Poland in the years 1934-1991 and their continuation under a changed name as the World Polonia Games in the years 1997-2015. The World Polonia Games are closely related to communities of the Polish diaspora, called Polonia, located in several dozen countries around the world. These people, generally maintaining a sense of connection with the Motherland, formed various social, religious, educational, cultural and youth associations. Among the latter, sports organizations played an important part. The objectives of physical culture related Polonia associations usually emphasized the need for and the significance of their cooperation with the sports movement in the home country. It was established through central institutions representing the interests of the Polonia community. This cooperation was aimed at mutual support of both the Polonia sports and competitive sports in Poland. The aim of this work is to present a timeline of events related to the organization and the course of the Summer World Polonia Games (1934-2015). The concept adopted by the authors stems not only from the extensive chronology, but also from the vastness of the source material. Many athletes representing various Polish diaspora communities participated in the Polonia Sports Games, and later in the Summer World Polonia Games. The program of the Games underwent gradual changes. The initially determined sporting performance minimums, which were to determine who should qualify for the Games were lifted. Age categories were extended in order to enable young, middle-aged and older people to take part in the Games. The Polonia Games gave impetus to association of Polish athletes in Polonia sports organizations abroad and contributed largely to the consolidation of Polish national life in exile. Polonia activists together with sports activists in Poland decided to continue the World Polonia Games for the sake of the whole Polish diaspora and Poles living in Poland.